A REVOLUTION OF CORPORATE GOVERNANCE IN INDONESIA SINCE 2000-2015 - Fadilah Risqy Utami Jeddawi (Jurnal Pallangga Praja (JPP), 2020)
ABSTRACTThe purpose of this study is to study the revolution of Corporate Governance in Indonesia since 2000- 2015. This study began with analyzing and comparing the perception survey from corporate governance perception index in order to examine the implementation of corporate governance revolution in Indonesia since the era of democratization and also to identify the factors of revolutionary movements since the era of democratization. The analysis found since 2000-2015 the implementation of corporate governance show that in general participants companies have committed CGPI (Corporate Governance Perception Index) to acheve performance targets. The findings of this study would be useful to several parties such as external and internal parties.Keywords: revolution, corporate governance, democratization, performance targets